Penerapan Praktik Akuntansi di Dinas Perindustrian dan Perdagangan: Studi Literatur - Siti Ramadhani Saragih; Nurlaila Nurlaila (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The Department of Industry and Trade (Disperindag) plays a crucial role in advancing the industrial and trade sectors at the local level. However, the implementation of accounting practices in government institutions often faces various significant and complex challenges. This literature study aims to present a comprehensive analysis of the application of accounting practices at the Department of Industry and Trade (Disperindag) by exploring various aspects of the accounting system implemented in the institution. This research employs a literature study method. In general, the accounting system applied at Disperindag has adhered to the applicable government accounting principles, including transaction recording, budget management, and reporting in accordance with established standards. However, there are several practices that need to be updated to align with the latest standards in order to enhance compliance. Although the financial reporting procedures are quite good, there are shortcomings in terms of speed and accuracy that can affect data-driven decisions. Budget management also faces challenges that require adjustments to enhance efficiency and effectiveness; recommendations for improving the accounting system at the Department of Industry and Trade are suggested. The increase in training for accounting staff is considered crucial to ensure they have a better understanding of regulations and best practices. In addition, updates in information technology are expected to accelerate and simplify the financial reporting process. A revision of the reporting and budget management procedures is also necessary to enhance the efficiency and effectiveness of budget utilization. The implementation of these recommendations is expected to improve the quality of the accounting system at the Department of Industry and Trade, enhance transparency and accountability, and support the achievement of the agency's strategic goals more effectively. Thus, financial management at the Department of Industry and Trade can become more optimal and contribute to sustainable economic development.